Análise de desempenho do tubo capilar num sistema de refrigeração de pequeno porte com variação da velocidade do compressor - Alegrias, Juan Gabriel Paz (2009)
The need to reduce energy consumption in refrigeration and air conditioning is a priority for the refrigeration industry. This has encouraged the development of refrigeration systems more efficient and offer better performance. In this context, increases the importance of applying new technologies to a deeper understanding of these systems and the improvement and optimization of cooling processes. Therefore, the monitoring and control of the operating conditions of a refrigeration system for vapor compression small cooling fluid, which operates with variable speed compressor, capillary tube as an expansion and uses R134a as refrigerant, this work, studies the behavior of the cooling system and examines the influence of changing the size of the capillary and rotational speed of the compressor from the point of view of performance and power consumption. The results, product analysis of response surfaces show how an optimal criteria combination results in better system performance.